2019
DOI: 10.1093/arclin/acy101
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Effects on White Matter Microstructure in Young Adults

Abstract: Objective Nicotine use is widely prevalent among youth, and is associated with white matter microstructural changes as measured by diffusion tensor imaging (DTI). In adults, nicotine use is generally associated with lower fractional anisotropy (FA), but in adolescents/young adults (≤30 years), microstructure appears healthier, indicated by higher FA. This cross-sectional study examined associations between nicotine use and white matter microstructure using fractional anisotropy (FA), mean dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…Regular cannabis use has been consistently linked to decreased FA and other DTI-derived diffusion estimates (Gruber et al 2014;Jacobus et al 2013a;Jacobus et al 2013b;Jakabek et al 2016;Orr et al 2016); however, this is less consistent among regular NTP users. In fact, several studies report increased FA among NTP users (Jacobsen et al 2007;Kangiser et al 2019;van Ewijk et al 2015;Yu et al 2016) and suggest that stimulation of acetylcholine receptors (nAChRs) via nicotine use may result in the promotion of some neurodevelopmental processes, including glial activity (Garrido et al 2003;Liu et al 2005) that support maturation of white matter (Dwyer et al 2009). Furthermore, nicotine may be distinct in how it acts on the adolescent brain compared with earlier and later developmental stages, including how it interacts with other endogenous systems such as the endocannabinoid system (Scherma et al 2016), which also plays a significant role in neurodevelopment (Meyer et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular cannabis use has been consistently linked to decreased FA and other DTI-derived diffusion estimates (Gruber et al 2014;Jacobus et al 2013a;Jacobus et al 2013b;Jakabek et al 2016;Orr et al 2016); however, this is less consistent among regular NTP users. In fact, several studies report increased FA among NTP users (Jacobsen et al 2007;Kangiser et al 2019;van Ewijk et al 2015;Yu et al 2016) and suggest that stimulation of acetylcholine receptors (nAChRs) via nicotine use may result in the promotion of some neurodevelopmental processes, including glial activity (Garrido et al 2003;Liu et al 2005) that support maturation of white matter (Dwyer et al 2009). Furthermore, nicotine may be distinct in how it acts on the adolescent brain compared with earlier and later developmental stages, including how it interacts with other endogenous systems such as the endocannabinoid system (Scherma et al 2016), which also plays a significant role in neurodevelopment (Meyer et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While the vast majority of studies focus on FA as the primary measure of white matter integrity, FA is sensitive to the complex geometry of white matter, including the crossing and merging of fiber tracts which can result in lower anisotropy estimates; thus, comprised tissue integrity cannot be unequivocally linked to reduced FA values (Pierpaoli et al 2001). Regular nicotine use in adolescent samples is typically associated with an increase in FA (Jacobsen et al 2007;van Ewijk et al 2015;Yu et al 2016), although not exclusively (Kangiser et al 2019), whereas regular cannabis use in adolescence is largely associated with reduced FA (Gruber et al 2014;Jacobus et al 2013b) or no effect (Cousijn et al 2012;Orr et al 2016;Thayer et al 2017) when comparing cannabis users to controls. Daily cigarette smoking in adults has also been associated with an increase in FA; however, greater nicotine dependence and smoking history in this sample were shown to be associated with reduced FA in regions such as the internal capsule and anterior cingulum (Hudkins et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As noted in the exclusion criteria, participants were excluded for excessive other drug use (>20 episodes in their lifetime for each drug category). In addition, included participants reported substance use that is consistent with age-based normative use (e.g., in the past year, 200–240 standard drinks [ 48 ]) or lower than in studies of emerging adult substance use (e.g., 3,000 cigarettes in the past year [ 49 ] or using cannabis at least 5 days per week [ 50 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies have contributed important insights into the structural, biochemical, and functional brain alterations associated with smoking in younger adults [10][11][12][13][14][15][16][17]. For example, a diffusion tensor imaging study [10] has shown lower fractional anisotropy (FA) in several neuronal fibres in the left hemisphere, which was also associated with impaired attention/working memory performance in smokers as compared to non-smokers. Another functional MRI (fMRI) study demonstrated the impact of smoking on prefrontal attentional brain networks [11], with smokers showing a significantly reduced prefrontal attentional network activity.…”
Section: Introductionmentioning
confidence: 99%